Parbukalo in Minangkabau Marriage Agreements: An Islamic Legal Perspective - Yusrial, Yusrial; Junaidi, Junaidi; Norcahyono, Norcahyono; Bachri, Indra; Husni, Muhammad Faruq Amarullah al; Indra, Novis (Suluah Pasaman, 2026)
Local wisdom represents a vital cultural capital that shapes social practices and beliefs within communities. The Minangkabau ethnic group in West Sumatra maintains diverse traditions, including parbukalo in marriage agreements. This study investigates the phenomenon of parbukalo from the perspective of Islamic law. Employing a qualitative method with a content analysis approach, data were collected from classical Islamic texts, scholarly works, and opinions of ushul fiqh experts. The findings reveal that the cultural phenomenology of ethnic marriage in Minangkabau, specifically parbukalo, does not fulfill the requirements of validity under Islamic law. Consequently, its implementation is not obligatory, as it contradicts the principles of Shari‘ah. This research provides preliminary insights for future studies on the intersection of local wisdom and Islamic legal frameworks across diverse socio-cultural contexts.